Centrally acting antihypertensives change the psychogenic cardiovascular reactivity. (27th February 2021) - Mendonça, Michelle M.; Costa, Amanda N.; Moraes, Gean C.A.; Martins, Gustavo M.; Almeida, Aline F.; Rincon, Gabriel C.N.; Siqueira, João P.R.; Padilha, Daniella M.; Moya, Marcela I.; Ferreira‐Neto, Marcos L.; Gomes, Rodrigo Mello; Pedrino, Gustavo Rodrigues; et al.
Abstract: Clonidine (CL) and Rilmenidine (RI) are among the most frequently prescribed centrally acting antihypertensives. Here, we compared CL and RI effects on psychogenic cardiovascular reactivity to sonant, luminous, motosensory, and vibrotactile stimuli during neurogenic hypertension. The femoral artery and vein of Wistar (WT – normotensive) and spontaneously hypertensive rats (SHR) were catheterized before (24 h interval) i.p. injection of vehicle (NaCl 0.9%, control ‐ CT group), CL (10 µg/kg), or RI (10 µg/kg) and acute exposure to luminous (5000 lm), sonant (75 dB sudden tap), motor (180° cage twist), and air‐jet (10 L/min – restraint and vibrotactile). Findings showed that: (i) CL or RI reduced the arterial pressure of SHR, without affecting basal heart rate in WT and SHR; (ii) different stimuli evoked pressor and tachycardic responses; (iii) CL and RI reduced pressor response to sound; (iv) CL or RI reduced pressor responses to luminous stimulus without a change in peak tachycardia in SHR; (v) cage twist increased blood pressure in SHR, which was attenuated by CL or RI; (vi) air‐jet increased pressure and heart rate; (vii) CL or RI attenuated the pressor responses to air‐jet in SHR while RI reduced the chronotropic reactivity in both strains. Altogether, both antihypertensives relieved the psychogenic cardiovascular responses to different stimuli. The RI elicited higher cardioprotective effects through a reduction in air‐jet‐induced tachycardia.